Physical-mechanical properties and the hydrogen absorption of irradiated by a pulsed electron beam zirconium alloy Zr-1% Nb; 16th International Symposium on High Current Electronics, Tomsk, 19-24 September 2010 - Lider A. M. Andrey Markovich; Chernov I. P. Ivan Petrovich; Cherdantsev Yu. P. Yuriy Petrovich; Pushilina N. S. Natalia Sergeevna; Stepanova O. M. Olga Mikhailovna; Garanin G. V. Georgy Viktorovich (2010, 2010)
The research of physical and mechanical products` properties made of zirconium alloy Zr-1 % Nb, irradiated by pulsed electron beams (PEB), was carried out, the processes of hydrogen absorption by these structures were reviewed, the influence of hydrogen on the properties of the coatings was studied. Theoretical calculations of thermal fields during the pulse irradiation were carried out. The influence of powerful pulsed electron beams on the material provided, its layer in thickness of the path order of the electrons is very quickly heated to the temperature of phase transitions, so that according to our calculations the maximum surface temperature during irradiation is 3250 K, under these conditions structural changes may occur at the depth of 40 μm. At the end of the beam pulse the heated layer is rapidly cooled by heat conduction into the depth of the material, the maximum cooling rate (Vcc ~ 108 K/s) is achieved in the thin surface layer of 1 μm thickness. Hydrogenations of zirconium alloy were performed from the gas phase in Sieverts-type apparatus and by electrolysis charging. It was established that irradiation of the surface leads to decrease in hydrogen absorption of 2.5-3 times in the specimen as to compare to non-irradiated material, charged with hydrogen.